1994
DOI: 10.1021/bi00206a037
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Mutated Transforming Growth Factor-.beta.s Which Possess Unique Biological Properties

Abstract: Transforming growth factor-beta (TGF-beta) is a potent regulator of cell growth and differentiation. On the basis of the crystal structure of TGF-beta 2, we have designed and synthesized two mutant TGF-beta s, TGF-beta 1 (71 Trp) and TGF-beta 1 (delta 69-73). Although both of these molecules inhibited the growth of Mv1Lu mink lung epithelial cells and LS1034 colorectal cancer cells, which are affected equally by TGF-beta 1 and TGF-beta 2, TGF-beta 1 (delta 69-73) was much less potent than TGF-beta 1 or TGF-bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Residues 69-73 from the other subunit contribute to the electrostatic potential around N2. Qian et al (1994) showed that the deletion of these residues had a profound effect on the biological activities of TGF-0 1, indicating that this area might be involved in the recognition. It is possible that Asp 23, Gln 26, and Asp 27 are involved in the recognition as well, because they possess different electrostatic potentials in TGF-02 and TGF-03, and are located close to residues 69-73.…”
Section: Potential Receptor Recognition Sitesmentioning
confidence: 99%
“…Residues 69-73 from the other subunit contribute to the electrostatic potential around N2. Qian et al (1994) showed that the deletion of these residues had a profound effect on the biological activities of TGF-0 1, indicating that this area might be involved in the recognition. It is possible that Asp 23, Gln 26, and Asp 27 are involved in the recognition as well, because they possess different electrostatic potentials in TGF-02 and TGF-03, and are located close to residues 69-73.…”
Section: Potential Receptor Recognition Sitesmentioning
confidence: 99%
“…The other domain (amino acids 69 -73) is important for receptor binding in the colorectal cancer cell line LS513 (33). Deletion of amino acids 69 -73 of TGF-␤1 dramatically decreased its binding to TGF-␤ receptors in this cell line, but not on other cells such as Mv1Lu cells and another colorectal cancer cell line, LS1034.…”
Section: Binding Competition Of Tgf-␤ Mutants With 125 I-tgf-␤1 For Mmentioning
confidence: 86%
“…Construction of expression plasmids for TGF-␤2/␤1-(40 -82), TGF-␤2/ ␤1-(40 -47), TGF-␤1-(⌬69 -73), and TGF-␤1-(Trp 71 ) has been previously described (31)(32)(33). Expression constructs of TGF-␤1/␤2-(40 -112), TGF-␤1/␤2-(83-112), TGF-␤1/␤2-(91-96), TGF-␤2/␤1-(83-112), and TGF-␤2/ ␤3-(40 -82) were generated using a two-step overlapping polymerase chain reaction method (31).…”
Section: Synthesis and Purification Of Recombinant Tgf-␤ Mutantsmentioning
confidence: 99%
See 2 more Smart Citations